Mengembangkan Inovasi Teknologi, Edukasi Sosial Dan Penguatan Nilai Keagamaan Melalui Pengabdian Mahasiswa Di Kelurahan Sukajadi Timur - ., Muhtarom; Ristianti, Dinda Ayu; Shanti, Aulia Berliana; Hasanah, Mesya Uswatun; Okta Rio, Awang Pramana; Rahmawati, Yoniza (CV. ITTC INDONESIA, 2026)
The Community Service Program (Kuliah Kerja Nyata/KKN) is a form of student community engagement through the direct application of knowledge in society. This activity aims to support the development of Sukajadi Timur Village through technological innovation, social education, and the strengthening of religious values. The method used was a participatory approach through observation, socialization, training, and community assistance. The programs implemented included the development of a village profile website, website management training, basic computer education for youth, literacy education, assistance in Business Identification Number (NIB) registration for micro, small, and medium enterprises (MSMEs), geographic information system-based village mapping, and mosque cleaning activities. The results of the activities indicate an improvement in community digital literacy, increased business legality among MSMEs, and enhanced community participation in social and religious activities. The Qur’an learning program that had been planned was not implemented due to institutional policy changes during the implementation period of the KKN. Overall, the KKN program contributed positively to community empowerment and the sustainable development of the village’s potential.